2001
DOI: 10.1055/s-2001-18148
|View full text |Cite
|
Sign up to set email alerts
|

Arachnoid Cysts: Entrapped Collections of Cerebrospinal Fluid Variably Communicating with the Subarachnoid Space

Abstract: Despite decades of investigation and discussion of the mechanisms involved in the pathophysiology of arachnoid cysts, fundamental issues concerning these entities remain poorly defined and controversial. Cine-mode magnetic resonance imaging (MRI) has shown two patterns of cerebrospinal fluid (CSF) flow within the cavity in patients harbouring arachnoid cysts. Some cysts present a harmonic flow with a patent flow entry zone. All these patients had intermittent, non-progressive and non-localizing symptoms requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 13 publications
0
9
0
3
Order By: Relevance
“…Os casos descritos na literatura, em que os CAMs foram adquiridos após trauma, haviam feito mielografia antes de adquirir o cisto (Schmidt et al, 2007). Outra teoria levantada na medicina veterinária é que alguns pacientes adquirem o cisto congenitamente, porém apresentam sintomatologia associada a ele após contusão ou leve trauma (Galloway et al, 1999;Santamarta et al, 2001;Vernau et al, 2002). Esta teoria pode ter ocorrido na paciente deste relato, visto que apresentou crises de dor na coluna, sem diagnóstico da causa na época, anos antes da contusão.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Os casos descritos na literatura, em que os CAMs foram adquiridos após trauma, haviam feito mielografia antes de adquirir o cisto (Schmidt et al, 2007). Outra teoria levantada na medicina veterinária é que alguns pacientes adquirem o cisto congenitamente, porém apresentam sintomatologia associada a ele após contusão ou leve trauma (Galloway et al, 1999;Santamarta et al, 2001;Vernau et al, 2002). Esta teoria pode ter ocorrido na paciente deste relato, visto que apresentou crises de dor na coluna, sem diagnóstico da causa na época, anos antes da contusão.…”
Section: Discussionunclassified
“…Em humanos, acredita-se em casos congênitos, secundários a trauma, infecções, hemorragias na subaracnoide, punção da mielografia ou associados a outras lesões como disrrafismo espinhal (Nabors et al, 1988;Santamartaet al, 1995;Santamarta et al, 2001). Na veterinária, foram descritos casos congênitos (Rylander et al, 2002), após trauma, fratura (Skeen et al, 2003;Sugiyama e Simpson, 2009), cirurgias descompressivas do disco intervertebral (Rylander et al, 2002), e associadas ainda à espinha bífida (Jurina e Grevel, 2004), siringomielia (Galloway et al, 1999;Skeen et al, 2003), discoespondilite e espondilomielopatia cervical (Skeen et al, 2003).…”
unclassified
See 1 more Smart Citation
“…It was reported that Cine-MRI as a new comer had identical effect as cisternography. We believe that Cine-MRI, as a new diagnostic means, with its more and more extensive application in clinical practice, will have great impact on the selection of surgical treatments in the future [9][10][11] . Our study indicated that epileptic seizure was also a common symptom of MCFAC.…”
Section: Discussionmentioning
confidence: 99%
“…This unusual postoperative complication has occasionally been described in the literature from different perspectives. [1][2][3] Case presentation Case 1. A 65-year-old man was admitted to our department following a generalised epileptic fit.…”
Section: Introductionmentioning
confidence: 99%